THE INFLUENCE OF RETURN ON EQUITY, DEBT EQUITY RATIO, CURRENT RATIO, FIRM SIZE, AND PRICE EARNING RATIO ON STOCK PRICES OF MANUFACTURING COMPANIES IN THE CEMENT SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE (PERIOD 2018-2022) - Sigit Mareta; Vivi Demitria Olla (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2023)
The capital market in Indonesia currently shows progress for the Indonesian economy. The capital market plays a crucial role as a means for business financing or obtaining funds from investors. Cement companies often serve as major contributors to a country's economy. This research aims to examine the influence of Return On Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), Firm Size, and Price Earning Ratio (PER) on the stock prices of manufacturing companies in the cement sub-sector listed on the Indonesia Stock Exchange during the period 2018-2022. The sample used consists of 6 companies. The research results provide evidence that Return On Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) have an impact on stock prices. However, Firm Size and Price Earning Ratio (PER) do not affect stock prices. This research can enhance our understanding of the variables influencing stock prices.